Apreensão apreciativa do discurso de outrem: autoria no processo de construção do conhecimento científico por professores concluintes de Letras - Leitão, Poliana Dayse Vasconcelos (2013)
In the academic and scientific context, the construction process of scientific knowledge is carried out through research, comprising basically three stages: planning, execution and research record - our object of study. Our main objective is to investigate the relation between the marks of appreciative apprehension of the discourse of others, the establishment of authorial stance and the construction process of scientific knowledge in monographs developed by undergraduating teachers of the Major in Portuguese/English. To achieve our goal, we conducted a documentary research on a midsize private faculty located in Bahia, where we worked as teacher, and collected data from an action research that we conducted during the master's course at the same institution. We organize the results of our research into five chapters. They are: 1) The construction of scientific knowledge in the teacher education in the 21st century (DEMO, 2005, 2006 and 2009; FREIRE, 1967 and 2010; GAUTHIER, 2006; PERRENOUD, 2008; SHULMAN, 2005; TARDIF, 1991, 2000, 2002 and 2005; ZABALZA, 2004a, 2004b and 2006); 2) Scientific Progress: from the fragmentation to the reintegration of man/nature/cosmos (ARANHA and MARTINS, 1992; BORTONI-RICARDO, 2008; DEMO, 1995; ECO, 2012; GARDNER, 2007; LAVILLE and DIONNE, 1999; LAKATOS and MARCONI, 2003; SALOMOM, 2004; SEVERINO, 2000); 3) The construction of knowledge in the light of the Socio-discursive Interacionism (BRONCKART, 1999, 2006 and 2008; MACHADO and GUIMARÃES, 2009; MACHADO and BRONCKART, 2009); 4) Dialogism: constitutive principle of authorship and construction of scientific knowledge (BAKHTIN/VOLOCHINOV, 2002; BAKHTIN, 2000/2003, 2002, 1993/2010; CHARTIER, 1998a and 1998b; FOUCAULT, 2002); and 5) Authorship: evidence of the theoretical and practical domain, of ethical commitment and aesthetic expression of the author. The results show us the difficulties of students not necessarily in relation to the monograph genre, but mainly in relation to the construction of scientific knowledge and the adoption of a high level of authorship. In five (55.55%) of the nine analyzed monographs, the graduating students are limited to paraphrase, structurally or semantically, the discourse of others, retrieving its content, and reproduce the scientific knowledge diffused in it. In two of them (22.22%), the authors, by paraphrase-comment, retrieve not only the content but also the expression of the discourse of others and apply the scientific knowledge acquired in the data analysis. In one of the monographs (11.11%), the author summarizes, analyzes and assumes a critical and reflective attitude towards scientific knowledge in order to investigate it, question it, complement it and/or (re)build it. And in one monograph (11.11%), the author retrieves, analyzes, evaluates the discourse of others and attributes to this discourse his/her intonation, expressiveness. Thus, in addition to (re)build scientific knowledge, the author impregnates it with his/her linguistic-discursive marks. In view of these results, we find out that, from the theoretical point of view, the research and, consequently, the construction of scientific knowledge and the critical-reflective attitude are defended in numerous documents, official or not, as formative principles that, in the academic field, should be linked to teaching and extension. However, from a practical point of view, we urgently need to rethink the practice of research, construction of scientific knowledge and authorial stance in the process of teacher education, especially in the process of language teachers education.